ANALISIS PERILAKU PETANI DALAM MENABUNG DI PT. BANK DANAMON INDONESIA TBK, UNIT DANAMON SIMPAN PINJAM PASAR BAGAN BATU - Donald Jhon Frengki; Ahmad Rifai; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This reaserch aimed to know level of importance of belief, evaluation,normative belief, motivation attitude and behavior of farmers for saving productsPT. Bank Danamon Indonesia Tbk, Unit Danamon Simpan Pinjam Pasar BaganBatu. Source of data was primary data from interview with respondents usingaccidental sampling. The data was analysis by fishbein model show consumer'sattitude to certain object and to know consumer's decision making process. Thisfishbein model explain of belief and evaluation of atribut PT. Bank DanamonIndonesia Tbk, Unit Danamon Simpan Pinjam Pasar Bagan Batu used includedinterest rates, promotion, gifts, location, friendliness of employees, savingadministration of processes, service employees and government guarantees.The dominant atribut was fill up by consumer's in belief is promotion andevaluation is interest rates. The result showed that absolute behaviour (AB) scored13.79, subjective normative (SN) scored 0.57 and behaviour intention (BI) scored532.62. The positive value of BI (>0) indicated that behaviour intention to savingproducts PT. Bank Danamon Indonesia Tbk, Unit Danamon Simpan Pinjam PasarBagan Batu is good. The most important variable of belief is promotion, andvariable of evaluation is interest rates. Referent which gives effect to the normativebelief variables and the neighbors of the first rank is the motivation variablereferents legality product.Keywords : Saving Money, Consumer Behaviour, Fishbein Model